MHC class i-restricted cytotoxic lymphocyte responses induced by enterotoxin-based mucosal adjuvants - Simmons, C; Mastroeni, P; Fowler, R; Ghaem-Maghami, M; Lycke, N; Pizza, M; Rappuoli, R; Dougan, G (American Association of Immunologists, 1999)
The ability of enterotoxin-based mucosal adjuvants to induce CD8+ MHC class I-restricted CTL responses to a codelivered bystander Ag was examined. Escherichia coli heat-labile toxin (LT), or derivatives of LT carrying mutations in the A subunit (LTR72, LTK63), were tested in parallel with cholera toxin (CT) or a fusion protein consisting of the A1 subunit of CT fused to the Ig binding domain of Staphylococcus aureus protein A (called CTA1-DD). Intranasal (i.n.) immunization of C57BL/6 mice with CT, CTA1-DD, LT, LTR72, LTK63, but not rLT-B, elicited MHC class I-restricted CD8+ T cell responses to coadministered OVA or the OVA CTL peptide SIINFEKL (OVA257–264). CT, LT, and LTR72 also induced CTL responses to OVA after s.c. or oral coimmunization whereas LTK63 only activated responses after s.c. coimmunization. rLT-B was unable to adjuvant CTL responses to OVA or OVA257–264 administered by any route. Mice treated with an anti-CD4 mAb to deplete CD4+ T cells mounted significant OVA-specific CTL responses after i.n. coadministration of LT with OVA or OVA257–264. Both 51Cr release assays and IFN-γ enzyme-linked immunospot assays indicated that IFN-γ−/− and IL-12 p40−/− gene knockout mice developed CTL responses equivalent to those detected in normal C57BL/6 mice. The results highlight the versatility of toxin-based adjuvants and suggest that LT potentiates CTL responses independently of IL-12 and IFN-γ and probably by a mechanism unrelated to cross-priming.